THERMAL MODIFICATION OF BAMBOO: EFFECTS ON PHYSICAL, MECHANICAL, AND CHEMICAL PROPERTIES - Suri, Intan Fajar; Hidayat, Wahyu; Febryano, Indra Gumay (Jurnal Belantara, 2025)
Bamboo is one of the most abundant non-timber resources, flourishing globally across tropical and subtropical regions. Its increasing appeal lies in its environmental sustainability, robust mechanical properties, and high recyclability. Nonetheless, bamboo's inherent hydrophilicity presents significant challenges, particularly in achieving optimal compatibility for applications such as construction materials. Economic and environmentally friendly heat treatment techniques have emerged as pivotal strategies for improving bamboo's surface properties. This article comprehensively reviews the effects of varying thermal treatment conditions, including temperature, duration, and medium, on bamboo's structural characteristics.